Sectoral diversification of~UAE~toward a~knowledge-based economy - Shamim Ahmad Siddiqui; Munshi Naser Ibne Afzal (Review of Economics and Political Science (REPS), 2022)
Purpose - The purpose of this study is to look at the United Arab Emirates' (UAE's) progress toward economic diversification and becoming a knowledge-based economy. Design/methodology/approach - The World Development Indicators (WDI) and GlobalEconomy websites provided all secondary data for this paper. The data are largely used to highlight the UAE's current level of diversification and, consequently, the atmosphere for a knowledge economy transition necessary for sustainable development. Additionally, the study conducts a nonparametric estimation using DEA to identify the condition of four variables pertaining to the UAE's knowledge economy. The Herfindahl-Hirschman index (HHI) was utilized empirically in this study to determine the current state of diversity. Findings - According to this research, the UAE economy was reasonably diverse until recently. The number of patents and journal papers published per resident both add to the UAE's GDP. Furthermore, the UAE's information and communication technology (ICT) exports are inconsistent; a declining trend in the number of researchers and the education sector's continuous struggles are major concerns. Furthermore, Figure 1 in the introduction reinforces this conclusion by noting that construction and building remained the greatest employer of labor throughout the time period. This is a significant finding because, as illustrated in this research, low labor force participation in the education sector, combined with lower citizen participation in advanced education in the UAE, results in low scientific research and publications, with low knowledge output as patent applications. In general, the majority of the UAE's population is expat, and the extent to which locals and expats contribute to the overall advancement of education remains an open question. According to the data envelopment analysis (DEA) model, three variables in the knowledge economy are productive, and they are economic incentive and institutional regime, innovation systems and ICT. The findings of this article will aid policymakers in the UAE, and more generally in the Gulf Cooperation Council (GCC) region, in developing more successful policies that help in the growth of a knowledge- and innovation-based economy. Practical implications - This study is appropriate for UAE economic policymakers to monitor the state and policies required for the UAE's transition to a knowledge economy. Originality/value - This issue has rarely been addressed by the use of robust parametric and nonparametric processes, as well as robust data visualization tools.
Keywords: 330; 02; 05; DEA; Economic diversification; HHI; ICT; Innovation; Knowledge economy; UAE